Формування приватного укладу в аграрному секторі України - Збарських, В. К.; Єременко, Денис Володимирович; Еременко, Денис Владимирович; Yeremenko, Denys (Мелітополь: Вид-во Мелітопольська типографія «Люкс», 2017)
UK: В статті розглянуто теоретичні засади формування приватних сільськогосподарських виробництв в системі вітчизняної економіки. Автори дослідили наукові підходи до визначення понять «економічна модель» та «форма господарювання». Обґрунтовано необхідність оптимізації теоретичного інструментарію в процесі дослідження вітчизняної моделі аграрного виробництва. EN: This paper considers theoretical base of private agricultural production system in the domestic economy. The authors examined the scientific approach to the definition of "economic model" and "form of management." The article states that in emerging economies, public forms of agriculture are virtually absent. It absolutely dominated private individual form. They include farms. It is noted that collective forms of agriculture resulting from combining individual objects of private property for the purpose of sharing in economic activities. This individual owners consciously united to mitigate the competition and increase profit by using economies of scale of production. Studies have shown that in agriculture owing to the production processes of good motivation for creative work and owner-owner and the employee has a high economic importance. The author notes that in the literature there is no unity in terms of prospects for development of the sector of private farms. The author is convinced that the economic terms of position creating highly effective, competitive in domestic and foreign markets agricultural production sector of private farms have had promising. In the article the theoretical necessity of optimization tools in the study of national model of agricultural production. The author points out that the promising model of national agricultural economy should be seen as a combination of large private and collective farms and small agricultural farms.
Formation of private agricultural sector in Ukraine
Keywords: особисті селянські господарства; аграрна економіка; аграрне виробництво; конкурентоспроможність; понятійний апарат; private farms; agricultural economics; agricultural production; competitiveness; concept vehicle